Meningkatkan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Stad Berbantuan Media Takalintar Pada Materi Perkalian Siswa Kelas V SD Negeri Kaluku Bodoa - Nur Angriani; Haerul Syam; Andi Ardillah Wahyudi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is held in three meetings. This research was conducted at SD Negeri Kaluku Bodoa. The research instruments used in this study were observation, learning achievement tests and documentation. The results showed that in the first cycle, out of 31 students, only 21 students or 67.7% met the minimum completeness criteria (KKM) or were in the low category with an average score of 78.2, while in cycle II where out of 31 students there are 30 students or 97% have met the minimum completeness criteria (KKM) with an average value obtained of 87.1 or are in the good category.